Investigation of a Collisional Radiative Model for Laser-Produced Plasmas - Nicholas L. Wong; Fergal O’Reilly; Emma Sokell (Atoms, 2020)
Plasmas of a variety of types can be described by the collisional radiative (CR) model developed by Colombant and Tonan. From the CR model, the ion distribution of a plasma at a given electron temperature and density can be found. This information is useful for further simulations, and due to this, the employment of a suitable CR model is important. Specifically, ionization bottlenecks, where there are enhanced populations of certain charge states, can be seen in these ion distributions, which in some applications are important in maintaining large amounts of a specific ion. The present work was done by implementing an accepted CR model, proposed by Colombant and Tonon, in Python and investigating the effects of variations in the ionization energy and outermost electron subshell occupancy term on the positions of ionization bottlenecks. Laser Produced Plasmas created using a Nd:YAG laser with an electron density of ∼ne = 1021 cm−3 were the focus of this work. Plots of the collisional ionization, radiative recombination, and three-body recombination rate coefficients as well as the ion distribution and peak fractional ion population for various elements were examined. From these results, it is evident that using ionization energies from the NIST database and removing the orbital occupancy term in the CR model produced results with ionization bottlenecks in expected locations.